2020
DOI: 10.31729/jnma.4741
|View full text |Cite
|
Sign up to set email alerts
|

Health Seeking Behaviour among Medical Students in a Teaching Hospital of Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Medical students are more prone to suffer from various physiological and psychologicalproblems but rather than seeking for formal health care, they tend to do informal consultation andoften practice self medication. Thus, this study aimed to find out the health seeking behavior ofmedical students. Methods: This descriptive cross-sectional study was done among first and second year medicalstudents of a teaching hospital from September to November 2019 after taking ethical approvalfrom Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…A larger proportion of the participants in this study showed good health - seeking behavior, similar to findings by Bhandari and Chataut (2020) , where 75% of medical students showed good health - seeking behavior towards utilization of mental health services. The positive health - seeking behavior of the study participants was reflected in their positive attitude on mental health services.…”
Section: Discussionsupporting
confidence: 86%
“…A larger proportion of the participants in this study showed good health - seeking behavior, similar to findings by Bhandari and Chataut (2020) , where 75% of medical students showed good health - seeking behavior towards utilization of mental health services. The positive health - seeking behavior of the study participants was reflected in their positive attitude on mental health services.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that both Hungarian and international medical students who had chronic illnesses had the possibility to visit the GP. This finding was supported by a study which stated that students had symptoms of chronic diseases, such as respiratory, gastrointestinal, musculoskeletal symptoms or miscellaneous would come to visit the GP [ 29 ]. The same thing has also been described by previous studies which stated that health seeking behaviour among medical students might be influenced by the presence or absence of chronic diseases the students had [ 30 ].…”
Section: Discussionmentioning
confidence: 73%
“…The same opinion has been expressed in a study that students tend to avoid or delay disclosure, and they seek help because of the perceived risk to their future [ 6 , 16 ]. Meanwhile, in another study, it has been suggested that the reason for coming to professional healthcare was not because it would hinder the students’ studies or reduce their achievement because of the disease they were having [ 4 ], but they were reluctant to come to the GP for reasons of the type and level of the disease they were experiencing [ 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fear of contracting the infection, stigma, lockdown restrictions, and self medication can be the reasons for this reduction. 19 This reduction in health seeking behavior is alarming. This challenge can be addressed through prioritizing and facilitating the concept of tele-health that can improve the provision of health services There are numerous mental health problems including depression other than anxiety which were not addressed here.…”
Section: Discussionmentioning
confidence: 99%